A Reference Database of Standardised Continuous Lumbar Intervertebral Motion Analysis for Conducting Patient-Specific Comparisons - Breen, Alexander; De Carvalho, Diana; Funabashi, Martha; Kawchuk, Greg; Pagé, Isabelle; Wong, Arnold Y. L.; Breen, Alan (Frontiers in Bioengineering and Biotechnology, 2021)
Lumbar instability has long been thought of as the failure of lumbar vertebrae to maintain their normal patterns of displacement. However, it is unknown what these patterns consist of. Research using quantitative fluoroscopy (QF) has shown that continuous lumbar intervertebral patterns of rotational displacement can be reliably measured during standing flexion and return motion using standardised protocols and can be used to assess patients with suspected lumbar spine motion disorders. However, normative values are needed to make individualised comparisons. One hundred and thirty-one healthy asymptomatic participants were recruited and performed guided flexion and return motion by following the rotating arm of an upright motion frame. Fluoroscopic image acquisition at 15fps was performed and individual intervertebral levels from L2-3 to L5-S1 were tracked and analysed during separate outward flexion and return phases. Results were presented as proportional intervertebral motion representing these phases using continuous means and 95%CIs, followed by verification of the differences between levels using Statistical Parametric Mapping (SPM). A secondary analysis of 8 control participants matched to 8 patients with chronic, non-specific low back pain (CNSLBP) was performed for comparison. One hundred and twenty-seven asymptomatic participants’ data were analysed. Their ages ranged from 18 to 70 years (mean 38.6) with mean body mass index 23.8kg/m2. 48.8% were female. Both the flexion and return phases for each level evidenced continuous change in mean proportional motion share, with narrow confidence intervals, highly significant differences and discrete motion paths between levels as confirmed by SPM. Patients in the secondary analysis evidenced significantly less L5-S1 motion than controls (p<0.05). A reference database of spinal displacement patterns during lumbar (L2-S1) intersegmental flexion and return motion using a standardised motion protocol using fluoroscopy is presented. Spinal displacement patterns in asymptomatic individuals were found to be distinctive and consistent for each intervertebral level, and to continuously change during bending and return. This database may be used to allow continuous intervertebral kinematics to drive dynamic models of joint and muscular forces as well as reference values against which to make patient-specific comparisons in suspected cases of lumbar spine motion disorders.